Interpolation of weighted Banach lattices : a characterization of relatively decomposable Banach lattices - Cwikel, M. (Michael), 1948- (Memoirs of the American Mathematical Society ;, 2003)
Interpolation of weighted Banach lattices, by Michael Cwikel and Per G. Nilsson: Introduction Definitions, terminology and preliminary results The main results A uniqueness theorem Two properties of the $K$-functional for a couple of Banach lattices Characterizations of couples which are uniformly Calderon-Mityagin for all weights Some uniform boundedness principles for interpolation of Banach lattices Appendix: Lozanovskii's formula for general Banach lattices of measurable functions References A characterization of relatively decomposable Banach lattices, by Michael Cwikel, Per G. Nilsson and Gideon Schechtman: Introduction Equal norm upper and lower $p$-estimates and some other preliminary results Completion of the proof of the main theorem Application to the problem of characterizing interpolation spaces References.